Katalis Regenerasi Tanah Berbahan Dasar Nasi (Oryza sativa L.) Limbah Rumah Tangga dan Limbah Pertanian Ampas Tebu (Saccharum officinarum) dan Bonggol Jagung (Zea mays) Sebagai Solusi Regenerasi Tanah pada Area Tanah Pertanian yang Terdegradasi. - Hudzaifah Ayyash Syaamil; Widayoko, Agus (Jurnal Integrasi Sains dan Quran, 2025)
Productivity in the agricultural sector is declining due to poor soil quality, erosion, and nutrient deficiencies. Human factors and inadequate land management systems contribute to this decline. By 2024, the agricultural land area will reach 70 million hectares. Relatively poor soil quality can be one of the causes of low productivity on agricultural land in Indonesia. An effective innovation is needed to overcome this and reduce the impact of contamination from unmanaged waste piles. The research at Trensains Muhammadiyah Sragen High School focuses on creating soil regeneration catalysts using household and agricultural waste in Dawe village. Data was collected through a completely randomized design (CRD) experiment, using three samples with varying concentration ratios. Literature review and observation were used to compare soil regeneration catalyst content, ingredients, and concentration. The research proves that soil regeneration catalysts based on agricultural and household waste can effectively overcome soil degradation and optimally utilize organic waste. The results showed that a mixture with a catalyst and water ratio of 1:9 and 1:8 was able to increase soil pH to near-ideal values 6.5-7 and maintain soil moisture in the range of 40%-60%.